Hubungan Self-Efficacy Dan Kepatuhan Dengan Tingkat Ketercapaian Cardiac Rehabilitation Pada Pasien Coronary Artery Disease: The Relationship Between Self-Efficacy and Compliance with the Level of Cardiac Rehabilitation Achievement in Coronary Artery Disease Patients - Rusiati, Ina; Koto, Yeni (Indonesian Scholar Journal of Nursing and Midwifery Science (ISJNMS), 2025)
Introduction: Coronary artery disease is a non-communicable disease and the number one cause of death in the world. Coronary artery disease has an impact on various aspects of the sufferer's life. Physically, patients will feel tightness, get tired easily, experience sexual disorders and chest pain. To determine the relationship between self efficacy and compliance with the level of achievement of cardiac rehabilitation in coronary artery disease patients.  Methods: The research design used in this study is descriptive analytic using the cross-sectional method. The population in this study were all coronary artery disease patients at the Heart Polyclinic in Grha Permata Ibu Hospital in Depok from January to March 2024 a total of 5,229 patients. The technique used was purposive sampling. So the sample of this study was 98 respondents. This research instrument was obtained through a questionnaire sheet. Data analysis using chi-square test. .Results: Based on the results of self efficacy obtained p-value = 0,002 means p-value < α (0,05) and Compliance obtained p-value = 0,000 means p-value < α (0,05). Discussion: there is a relationship between compliance and the level of achievement of cardiac rehabilitation in patients with coronary artery disease.